Salacia reticulata (Kothala himbutu) revisited; a missed opportunity to treat diabetes and obesity? - Medagama, Arjuna B (Nutr J, 2015)
BACKGROUND: Nearly 50% of diabetic patients worldwide use complementary medicines to treat or supplement their conventional diabetes treatment. Salacia reticulata (Kothala himbutu) is a woody climber used widely in the Ayurvedic system to treat diabetes and obesity. OBJECTIVE: In this review I critically analyze the evidence for using Salacia reticulata for treating type 2 diabetes and obesity. The available evidence is described in terms of in-vitro studies, animal studies and clinical trials. RESULTS AND CONCLUSIONS: In vitro studies demonstrate the ability of Salacia to inhibit intestinal alpha glucosidase. In mouse mesenteric fat it enhances the mRNA expression for hormone sensitive lipase (HSL) and adiponectin; thus increasing lipolysis and reducing insulin resistance respectively. In 3 T3-L-1 adipocytes lipogenesis factors are down regulated and lipolysis factors are up regulated with Salacia reticulata treatment. Animal studies and clinical trials are consistent in demonstrating improvement of glucose concentrations in the fasted and sucrose and maltose loaded states. Clinically significant reductions of HbA1C and plasma Insulin are reported with treatment of 6 weeks to 3 months. One clinical trial reported significant reduction of weight and BMI when Salacia is used in combination with vitamin D. Salacia reticulata effectively improves insulin resistance, glucose metabolism and reduces obesity. A larger evidence base is required from well-planned studies to confirm its efficacy and safety.